Cloning of wheat keto-acyl thiolase 2B reveals a role of jasmonic acid in grain weight determination - Yun Chen (Nature Portfolio, 2020)
It has been reported that several phytohormones are involved in the regulation of grain weight, but the role of jasmonic acids (JA) remains elusive. Here, via bulked segregant analysis (BSA)-based cloning, the authors show keto-acyl thiolase 2B involved in β-oxidation during JA synthesis is a positive regulator of wheat grain weight.